The Play of Roots

Level pending

x 3 + 4 x 1 = 0 x^3 +4x -1 = 0 has roots α , β , γ \alpha , \beta, \gamma and 6 y 3 7 y 2 + 3 y 1 = 0 6y^3 -7y^2+ 3y -1 =0 where y = 1 x + 1 y= \frac {1}{x+1} . If ( β + 1 ) ( γ + 1 ) ( α ) 2 + ( γ + 1 ) ( α + 1 ) β ) 2 + ( α + 1 ) ( β + 1 ) ( γ ) 2 \frac {(\beta+1)(\gamma+1)}{(\alpha)^2} + \frac {(\gamma+1)(\alpha+1)}{\beta)^2} + \frac {(\alpha+1)(\beta+1)}{(\gamma)^2} can be expressed as a b \frac {a}{b} where a and b are coprime integers, find a + b a+b .


The answer is 109.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pi Han Goh
Dec 21, 2013

The expression equals

( α + 1 ) 3 ( β + 1 ) 3 + ( α + 1 ) 3 ( γ + 1 ) 3 + ( α + 1 ) 3 ( α + 1 ) 3 ( ( α + 1 ) ( β + 1 ) ( γ + 1 ) ) 2 \large \frac { (\alpha + 1)^3(\beta + 1)^3 + (\alpha + 1)^3 (\gamma + 1)^3 + (\alpha + 1)^3 (\alpha + 1)^3 }{ \left ( (\alpha + 1)(\beta + 1) (\gamma + 1) \right )^2}

= ( α + 1 ) ( β + 1 ) ( γ + 1 ) ( 1 ( α + 1 ) 3 + 1 ( β + 1 ) 3 + 1 ( γ + 1 ) 3 ) \large = (\alpha + 1)(\beta + 1)(\gamma + 1) \cdot \left ( \frac {1}{(\alpha + 1)^3} + \frac {1}{(\beta + 1)^3} + \frac {1}{(\gamma + 1)^3} \right )

Let f ( x ) = x 3 + 4 x 1 f(x) = x^3 + 4x - 1 , then f ( x ) f(x) has roots α , β , γ \alpha, \beta, \gamma .

f ( x 1 ) = ( x 1 ) 3 + 4 ( x 1 ) 1 = x 3 3 x 2 + 7 x 6 \begin{aligned} \Rightarrow f(x-1) & = & (x-1)^3 + 4(x-1) - 1 \\ & = & x^3 -3x^2 +7x - 6 \\ \end{aligned}

has roots ( α + 1 ) , ( β + 1 ) , ( γ + 1 ) (\alpha + 1), (\beta + 1), (\gamma + 1)

By Vieta's formula, ( α + 1 ) ( β + 1 ) ( γ + 1 ) = 6 (\alpha + 1)(\beta + 1)(\gamma + 1) = 6

Let g ( x ) = x 3 3 x 2 + 7 x 6 g(x) = x^3 - 3x^2 + 7x - 6 , then g ( 1 x ) = 0 g(\frac {1}{x} ) = 0 has roots 1 α + 1 , 1 β + 1 , 1 γ + 1 \frac {1}{\alpha + 1},\frac {1}{\beta + 1},\frac {1}{\gamma + 1}

1 x 3 3 x 2 + 7 x 6 = 0 6 x 3 7 x 2 + 3 x 1 = 0 \begin{aligned} \Rightarrow \frac {1}{x^3} - \frac {3}{x^2} + \frac {7}{x} - 6 & = & 0 \\ 6x^3 - 7x^2+3x-1 & = & 0 \\ \end{aligned}

has roots 1 α + 1 , 1 β + 1 , 1 γ + 1 \frac {1}{\alpha + 1},\frac {1}{\beta + 1},\frac {1}{\gamma + 1}

Recall the identity, X 3 + Y 3 + Z 3 3 X Y Z = ( X + Y + Z ) ( ( X 2 + Y 2 + Z 2 ) ( X Y + X Z + Y Z ) ) X^3 + Y^3 + Z^3 - 3XYZ = (X+Y+Z) \left ( (X^2+Y^2+Z^2) - (XY+XZ+YZ) \right )

In this case, let X , Y , Z X,Y, Z be 1 α + 1 , 1 β + 1 , 1 γ + 1 \frac {1}{\alpha + 1},\frac {1}{\beta + 1},\frac {1}{\gamma + 1}

X 3 + Y 3 + Z 3 3 ( 1 6 ) = ( 7 6 ) ( ( X + Y + Z ) 2 3 ( X Y + X Z + Y Z ) ) X 3 + Y 3 + Z 3 1 2 = ( 7 6 ) ( ( 7 6 ) 2 3 ( 3 6 ) ) X 3 + Y 3 + Z 3 = 73 216 \begin{aligned} \Rightarrow X^3 + Y^3 + Z^3 - 3\left ( \frac {1}{6} \right ) & = & \left ( \frac {7}{6} \right ) \left ( (X+Y+Z)^2 - 3(XY+XZ+YZ) \right ) \\ X^3 + Y^3 + Z^3 - \frac {1}{2} & = & \left ( \frac {7}{6} \right ) \left ( \left ( \frac {7}{6} \right )^2 - 3 \left ( \frac {3}{6} \right ) \right ) \\ X^3 + Y^3 + Z^3 & = & \frac {73}{216} \\ \end{aligned}

Hence, the expression equals to 6 73 216 = 73 36 6 \cdot \frac {73}{216} = \frac {73}{36}

The answer is 73 + 36 = 109 73 + 36 = \boxed{109}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...